Analisis Pengaruh Kualitas Produk dan Harga Produk terhadap Keputusan Pembelian Produk Parfum Hiour - Ahmad Yuda; Virda Kurnia Sari; Yustira Dwi Julianti; Fonny Yeisa Putri Pramudya Elang Saputra (PUTRA JAWA PUBLISHER, 2023)
This study aims to analyze the influence of product quality and product prices on the purchasing decision of Hiour Perfume products. This study is a quantitative study using the statistical SPSS program 22 with a total sample of 50 respondents. The results of this study show that product quality has a significant effect on purchasing decisions while product prices do not have a significant effect on purchasing decisions.